FIRST RECORDS OF THE INVASIVE AMERICAN WASP ISODONTIA MEXICANA (HYMENOPTERA: SPHECIDAE) IN SERBIA (Acta Entomologica Serbica, 2012)
The first verified occurrences of the invasive American sphecid wasp, Isodontia mexicana (Saussure, 1867), in Serbia are reported. It was first collected from a trap-nest sample in the northern surroundings of Belgrade in 2010. During 2012, we recorded well-established, abundant populations in the central city area of Belgrade, its surroundings, and also at a single site on the Fruška Gora Mt. We briefly review the circumstances and course of its recent eastward and northeastward spreading in Europe since1990, from Slovenia and Croatia to Hungary and Austria. Establishment of I. mexicana in northern Serbia and its probable range expansion further south represent the expected continuation of its spreading throughout western Europe, following its initial introduction into southern France around 1960.